Assessing the spatio-temporal climate variability in semi-arid Karamoja subregion in north-eastern Uganda - Egeru, Anthony; Osaliya, Richard; MacOpiyo, Laban; Mburu, John; Wasonga, Oliver; Barasa, Bernard; Said, Mohammed; Aleper, Daniel; Majaliwa Mwanjalolo, Gilbert-Jackson (International Journal of Environmental Studies, 2014)
Semi-arid areas show climatic variability on a spatio-temporal scale. There are few studies on the long-term trends and intensity of this variability from East Africa. We used National Ocean and Atmospheric Administration re-analysis climate data (1979–2009) in this study. Rainfall exhibited a non-significant long-term trend. The climate of the area is variable (coefficient of variation-CV >35.0%) with spatio-temporal oddities in rainfall and temperature. A rise in minimum (0.9 °C), maximum (1.6 °C) and mean (1.3 °C) temperature occurred between 1979 and 2009. There were more months with climate variability indices below the threshold (<1.0) from 1979 to 1994 than between 1995 and 2009, with wetness intensity increasingly common after 2000, leading to the observed reduction in the recurrence of multi-year drought events. More extreme wet events (rainfall variability index >2.6) were experienced between 2004 and 2009 than between 1984 and 2003. We consider that the use of spatio-temporal climatic information for timely adjustment to extreme climate variability events is essential in semi-arid areas.
Keywords: Climate variability; Forage; Variability index; Karamoja